Possible implications of dietary changes on nutrient fluxes, environment and land use in Austria. (June 2015) - Thaler, S.; Zessner, M.; Weigl, M.; Rechberger, H.; Schilling, K.; Kroiss, H.
Highlights: The impacts of a diet change on resources and environment have been modeled. A quantification of a reference period is used as basis for retrospective scenarios. A healthy balanced diet would result in a reduced area for food production by 37%. A healthy balanced diet would result in reduced demand for N and P by about 25%. A healthy balanced diet could reduce N loads exported via rivers by 15%. Abstract: Health recommendations clearly show that in Austria and other highly developed countries less animal and more plant based food should be consumed. A meat based diet is held responsible for a number of environmental problems. We explore the impacts on nutrient fluxes (nitrogen and phosphorus) and land use as the result of a change from a meat based diet to a healthier balanced diet consisting of less animal based products and more plant based food in Austria. We use a detailed material flow analysis and the nutrient emissions model MONERIS in combination with scenarios. The scenarios address differing farming methods, varying trade options and different use of potentially available agricultural area. Our findings show that overall, a shift to a healthy balanced diet leads to less land being used for agricultural production (−30%), less resource consumption (20% to 25% less phosphorus) and lower transfer of nutrients from agriculture into the environment compared to the reference situation. Total emissions of nitrogen and phosphorus into water decrease (between 15% and 11% for nitrogen and by 5% to 6% for phosphorus) and nitrogen concentrations in groundwater change substantially depending on the intensity of farming assumed by different scenarios.